Analisis Sistem Pencatatan Akuntansi Aktiva Tetap Pada PT Perkebunan Nusantara I Regional 1 - Angga; Ratna Sari Dewi; Debbi Chyntia Ovami (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This research was conducted at PT. Perkebunan Nusantara I Regional I located at Jl. Lintas Sumatra Km. 21, Limau Manis, District. Tanjung Morawa, Deli Serdang Regency. PT. Perkebunan Nusantara I Regional I is a State-Owned Enterprise (BUMN) engaged in the plantation sector with palm oil, sugar cane, rubber and tea commodities. The purpose of this study was to determine how to record fixed assets at PT Perkebunan Nusantara I Regional I. The research method used is a qualitative descriptive method, namely comparing the actual conditions with theories that are relevant to the related problems. Data collection and other information were carried out by interview and documentation. Based on the research conducted, it can be concluded that the company combines the acquisition value of goods such as lightning protection towers and concrete pipes with the acquisition price of installation costs. The combination of acquisition prices has an impact on the calculation and presentation of more substantial depreciation and operating costs, so that the profit calculated in the income statement is reduced. This results in a significant accumulation of depreciation on the balance sheet, resulting in a lower estimated book value.